"The Centerpiece of College Athletics": Prioritizing Education in the College Sports Reform Movement - Aaron Miller (University of Kansas Libraries, 2022)
This article, which is based upon long-term fieldwork observations of a big-time women's college basketball team, proposes reforms that would more sufficiently compensate the professional role big-time college athletes perform, all without sacrificing the educational connection that is vital to the core of college sports for men and women. It argues that colleges involved in big-time college sports should expect college athletes to be students first, allow them to earn pay for their names, images, and likenesses (NILs), and strike a better balance between providing education to athletes and entertainment to the public.